2011
DOI: 10.1007/s12032-011-9830-2
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant microRNA expression in human cervical carcinomas

Abstract: Because altered microRNAs (miRNAs) expression patterns have been observed in a variety of diseased tissues, miRNA expression was compared in human cervical cancer tissues relative to adjacent normal cervical tissues in the present study. Microarray chips with 924 probes were used to detect the expression of miRNAs in cervical cancer tissue and adjacent normal cervical tissue of 13 patients with cervical cancer (11 squamous cervical cancers, one cervical adenocarcinoma, and one cervical sarcoma), all of whom we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 26 publications
8
72
0
2
Order By: Relevance
“…We previously demonstrated that miR-214 was down-regulated in cervical cancer tissue and could negatively regulate HeLa cell growth (14,19). A new microarray analysis also indicated that miR-214 was down-regulated in cervical cancer tissue (20). Additionally, our previous cDNA microarray analysis indicated that GALNT7 increased up to 5.49-fold when miR-214 expression was suppressed in HeLa cells (19).…”
mentioning
confidence: 95%
“…We previously demonstrated that miR-214 was down-regulated in cervical cancer tissue and could negatively regulate HeLa cell growth (14,19). A new microarray analysis also indicated that miR-214 was down-regulated in cervical cancer tissue (20). Additionally, our previous cDNA microarray analysis indicated that GALNT7 increased up to 5.49-fold when miR-214 expression was suppressed in HeLa cells (19).…”
mentioning
confidence: 95%
“…However, some studies did not find this to be the case in cervical cancer tissues (Martinez et al, 2008;Li et al, 2011;Rao et al, 2012). Thus, the association of HR-HPV and miR-21 upregulation with cervical cancer development is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Patients that were enrolled in these studies had not received chemo-or radiotherapy prior to sample collection, which in most cases, occurred during surgery. In this regard, Rao et al [88] determined miRNA profiling of 26 matched cervical cancer and normal tissue samples collected from 13 patients. MiRNA gene expression of cervical cancer tissues and normal adjacent tissues was assessed using CaptialBio mammalian miRNA array V3.0 (CapitalBio, Beijing, China).…”
Section: Mirnas Expression In Pre-neoplasic Lesions and Cervical Cancermentioning
confidence: 99%